The Validity Of A Husband's Guardianship Over His Wife In The Sale And Purchase Of Land Rights Wife's Inherited Property (Case Study Ngawi District Court Number 14/Pdt.G./2019/PN Ngw) - Nadia Pitra Kinasih (Fakultas Hukum Universitas Jenderal Soedirman, 2025)
The transfer of land rights through sale and purchase is evidenced by the execution of a Sale and Purchase Deed (Akta Jual Beli) before a Land Deed Official (PPAT). This research aims to analyze the validity of a husband’s guardianship over his wife in the sale and purchase of land that constitutes the wife’s separate property, conducted without the consent of the heirs, as well as the liability of the PPAT in preparing a sale and purchase deed based on a guardianship determination without the heirs’ approval. The research method used is normative juridical research. The validity of guardianship that does not comply with the provisions of Article 434 Paragraph (1) of the Indonesian Civil Code has the potential to violate the rights of the heirs in the sale and purchase of the wife’s separate property. The execution of the sale and purchase deed creates issues for the PPAT, as negligence in preparing the deed based on a guardianship decision without valid heirs’ consent, whether intentional or not, can result in losses to other parties and give rise to civil and administrative liability. This study concludes that the husband’s guardianship over the wife in the sale and purchase of the wife’s separate property is formally defective because it contradicts statutory regulations, affecting the validity of the sale and purchase deed which does not meet material requirements. The actions taken by the PPAT are contrary to Article 16 Paragraph (1) Letter a of the Law on Land Deed Officials (UUJN), which requires that in preparing deeds, the PPAT must act honestly, faithfully, thoroughly, independently, impartially, and safeguard the rights and interests involved in the legal act.